Mpox-related stigma and healthcare-seeking behavior among men who have sex with men - Yujie Liu; Jiechen Zhang; Yong Cai (Global Health Research and Policy)
Abstract The 2022 global mpox outbreak highlighted significant public health challenges, with men who have sex with men (MSM) accounting for 86.7% of confirmed cases. As a high-risk group, MSM faced not only the direct health impacts of mpox but also an additional burden of stigma and discrimination, which severely hindered their willingness to seek care and access timely medical services. This article explores mpox-related stigma and discrimination and their profound impact on healthcare-seeking behaviors among MSM, drawing on evidence from global studies. We examine how stigma affects individual decision-making and has broader public health implications by exacerbating healthcare delays during the outbreak. In response, we propose actionable strategies to mitigate stigma, including providing accurate and responsible communication, strengthening community and social support network, building capacity for frontline workers, and engaging affected individuals for effective intervention. By integrating stigma-reduction measures into pandemic preparedness and response, public health systems can better support vulnerable populations, improve healthcare access, and ensure a more effective response to future outbreaks.